A case of eosinophilic granulomatosis with polyangiitis after prolonged intervals of an anti-interleukin-6 receptor antibody for rheumatoid arthritis. Issue 1 (11th August 2021) - Imai, Yuki; Kondo, Yasushi; Ishigaki, Sho; Nishina, Naoshi; Ota, Yuichiro; Hanaoka, Hironari; Kaneko, Yuko; Takeuchi, Tsutomu
ABSTRACT: An 83-year-old woman with a history of asthma complained of left abdominal pain and was admitted to our hospital. She was treated with tocilizumab, an anti-interleukin (IL)-6 receptor antibody, with a prolonged interval for rheumatoid arthritis (RA). Laboratory tests revealed a remarkable increase in eosinophil count and inflammatory markers with negative antineutrophil cytoplasmic antibodies. Echocardiography revealed pericardial fluid retention, and contrast-enhanced computed tomography revealed the thickening of the gastric antrum wall. Upper gastrointestinal endoscopy and biopsy revealed eosinophilic infiltration into the gastric mucosal epithelium. She was diagnosed with eosinophilic granulomatosis with polyangiitis (EGPA) with pericarditis and eosinophilic gastroenteritis. High-dose glucocorticoids with intermittent intravenous cyclophosphamide (IVCY) were initiated, resulting in remission. As IL-6 is involved in the pathogenesis of allergic diseases such as asthma, our case can provide insights into the pathogenic role of IL-6 in EGPA as the development of EGPA in our case may have been triggered by IL-6 signals enhanced with tocilizumab interval prolongation.